Mathematical Model of Malaria with Flooding in Thailand - Puntani Pongsumpun (My University, 2015)
Malaria is occurred by biting of infected Anopheles mosquitoes.Four species of Plasmodium are Plasmodium falciparum, Plasmodium vivax, Plasmodium ovale and Plasmodium malariae .This disease is found in tropical countries, especially Thailand.We consider the effect of flooding in Thailand with the transmission of Malaria disease.Mathematical model is formulated by using theory of modeling.The variables and parameters are defined corresponding to the characteristic of this disease.Our model is analyzed by using dynamical modeling method.Numerical simulations are shown comparing with the analytical solutions.
Keywords: Mathematical and Theoretical Epidemiology and Ecology Models